A blueprint of synergistic effect in Crataegus pinnatifida and obesity-related gut microbiota against obesity via systems biology concept - Jinghui Xie; Haofang Guan; Maohui Liu; Weijun Ding (PLoS ONE, 2025)
Background Current obesity treatments include behavioral interventions, pharmacotherapy and surgery. Recently, the combination of ‘medicinal food’ products such as the plant Crataegus pinnatifida and its interaction with the gut microbiota has shown promise as an alternative therapeutic strategy to treat obesity. Methods We obtained secondary metabolites (SMs) of obesity-related gut microbiota and Crataegus pinnatifida from gutMGene database and NAPSS database. bioinformatics analysis was used to elucidate key target and signaling pathways, whereas molecular docking (MD), molecular dynamics simulation and quantum chemical calculations identified crucial SMs involved in these pathways. The toxicity and physicochemical properties of these SMs were also assessed. Results Phosphoinositide-3-kinase regulatory subunit 1 (PIK3R1), a key mediator in the phosphoinositide 3-kinase (PI3K)/ Protein Kinase B (Akt) pathway that is crucial for regulating insulin signaling and adipogenesis, emerged as the central hub within the PPI network. Strong binders to PIK3R1 were predicted to be quercetin, kaempferol and naringenin chalcone, suggesting their potential as therapeutic agents to treat obesity. Conclusion The synergistic combination of Crataegus pinnatifida and the obesity-related gut microbiota holds promise as a novel therapeutic strategy for obesity by targeting PIK3R1 and modulating the PI3K/Akt signaling pathway. Further experimental validation is necessary to confirm these findings.